Multiobjective synthesis of robust control by multimass electromechanical systems based on Pareto-optimal solution - T.B. Nikitina (National Technical University "Kharkiv Polytechnic Institute", 2015)
A multiobjective method of synthesis of robust control of multimass electromechanical systems based on the construction of the Pareto-optimal solution is improved. A Pareto-optimal solution based on a stochastic multi-agent particles swarm optimization, which can significantly reduce the time for solving the problem and meet the diverse requirements that apply to the work of multimass electromechanical servo systems in different modes is founded. The results of comparisons of the dynamic characteristics of the electromechanical servo system with synthesized robust regulators are presented.